Tinjauan Yuridis Terhadap Plagiarisme Oleh Partai Politik Suatu Negara Berdasarkan TRIPs Agreement 1994 (Studi Kasus Plagiarisme Oleh Partai Nasional Selandia Baru) - Dany Ardy Saputra; Hilton Tarnama Putra M; Mas Nana Jumena (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2021)
TRIPs are one of the sources of International Law that is widely used by many countries in drafting international trade regulations. One of the things that is quite firmly regulated in TRIPs is the act of plagiarism. Today there have been many acts of plagiarism, no exception in the scope of the international community. Acts of plagiarism can also be done by anyone be it individuals, legal entities, or organization. One example of plagiarism violations occurring within the international copyright sphere is a case concerning New Zealand National Party with Eight Mile Style which is the publicist of international musician Eminem. Idetification of the problem in this study is how to set up acts of plagiarism by political parties according to TRIPs Agreement 1994 and how to solve cases acts of plagiarism by New Zealand National Party according to TRIPs Agreement 1994. This research method uses normative juridical methods that are qualitative. The research specifications used are analytical descriptive. Data collection techniques using literature study techniques and obtaining secondary data covering primary, secondary, and tertiary legal materials. Data analysis using qualitative data analysis. The conclusion of this study is that in TRIPs Agreement 1994 not including a regulation on political parties. As a legal or regulatory subject regarding plagiarism committed by political parties in resolving cases between Eight Mile Style which are legal entities and as the licensee of the song “Lose Yourself” who are suing New Zealand National Party who used the song as part of one of the party's campaign ads, in resolving the case using New Zealand Copyright Act 1994, this is in accordance with the Article 61 TRIPs Agreement 1994 stating that member states must regulate criminal procedures and penalties to be applied.